Grand Theft Auto IV Considered as an Atrocity Exhibition - Pichlmair, Martin (Eludamos: Journal for Computer Game Culture, 2008)
This review outlines the intersections between Rockstar Games' "Grand Theft Auto IV" (2008) and the British novelist J.G. Ballard's experimental text "The Atrocity Exhibition". Obvious parallels like the dominant roles of cars and carnage are supplemented by more subtle similarities. Grand Theft Auto is an Atrocity Exhibition, a deliberately instigated scandal and a cynical masterpiece.